1995
DOI: 10.1056/nejm199504133321503
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Nicotine as Maintenance Therapy for Ulcerative Colitis

Abstract: Transdermal nicotine alone was no better than placebo in the maintenance of remission of ulcerative colitis, and premature withdrawal due to side effects was more common in the nicotine group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
14

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 19 publications
0
105
0
14
Order By: Relevance
“…6,7 Transdermal nicotine patches added to conventional treatment with 5-aminosalicylic acid (5-ASA) have a bene®cial effect on active colitis, 8±10 but in the only published study, were of no bene®t for maintenance of remission. 11 Since 15 mg of transdermal nicotine causes substantial sideeffects in up to two-thirds of patients, 9±11 particularly lifelong non-smokers, attempts have been made to develop a therapy for colitis with a formulation which is effective and better tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Transdermal nicotine patches added to conventional treatment with 5-aminosalicylic acid (5-ASA) have a bene®cial effect on active colitis, 8±10 but in the only published study, were of no bene®t for maintenance of remission. 11 Since 15 mg of transdermal nicotine causes substantial sideeffects in up to two-thirds of patients, 9±11 particularly lifelong non-smokers, attempts have been made to develop a therapy for colitis with a formulation which is effective and better tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Nicotine vs. placebo patch. Three randomised controlled trials (RCTs), Pullan et al, 77 Sandborn et al 78 and Thomas et al 79 examined transdermal nicotine therapy compared to a placebo patch. Pullan et al 77 conducted a randomised, double-blind study in which 72 patients with active UC were treated with either nicotine patch or a placebo patch for 6 weeks.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…10 The negative Thomas study of the 15 mg patch/16 h reported that the respective mean week 26 trough plasma nicotine and cotinine concentrations were 5.3 ng/mL and 62 ng/mL. 12 Thus, in patients with ulcerative colitis treated with transdermal nicotine, higher serum or plasma nicotine concentrations are associated with a therapeutic effect. This is in contrast to patients treated with nicotine tartrate liquid enemas in whom the therapeutic effect is apparently unrelated to the serum nicotine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast, results from a controlled trial using a lower dose of transdermal nicotine (15 mg/16 h) for ulcerative colitis remission maintenance were no different than placebo. 12 Side-effects from transdermal nicotine were frequently noted in the studies discussed above and included contact dermatitis, nausea, vomiting, headaches, sleep disturbance, diaphoresis, tremor and lightheadedness. 9±12 Thus, although nicotine appears to be of bene®t as a therapeutic agent for active ulcerative colitis, long-term transdermal nicotine treatment is likely to be limited by side-effects.…”
Section: Introductionmentioning
confidence: 98%